Detecting child psychiatric disorders during routine clinic work: A pre-interventional study of primary care physicians in Ilorin, Nigeria - O A Abiodun; M F Tunde-Ayinmode; B A Ayinmode; O A Adegunloye (South African Journal of Psychiatry, 2011)
Back-ground Primary care physicians (PCP) are accessible health care provider for most patients and are gatekeepers to specialist care. The extent to which they can identify children with mental health problems need to be explored.